Health Security Ideas of Major Political Groups and the US Military Government during the Liberation Period (1945-1948) in Korea - Ye-mok JEON; Young-jeon SHIN (Uisahak, 2022)
The liberation period in Korea was when creative imagination and various debates existed about plans for political, economic, and social systems. Among them was the debate over the national health security underlying the social safety net. Although the US influenced the Korean health security after liberation, major political groups on the Korean peninsula also expressed various opinions. However, previous studies have shown little interest in national health security, which operates the public health and medical care systems. To overcome these limitations, this study focuses on the ideas on national health security presented by major political groups, analyzing the reply proposal of “Jŏnpyŏng” and the health care proposal of the US military government, which has not been reviewed before. The opinions of major political groups including the right-wing Im-hyŏp and left-wing Min-chŏn diverged on national health security issue regarding insurance coverage, measures to secure financial resources, items of insurance benefits, and measures to stabilize the supply and demand of medical personnel. The claims of the US military government can be understood by “Labor Problems and Policies in Korea (Korean Subcommittee),” “Korean Labor Report (Stewart Meacham),” and “Proposed Political Platform Provisional Korean Democratic Government (Sub-commission #2).” The major political groups and the US military government agreed on the need for social protection against death, old age, disability, disease, injury, and unemployment. All of them claimed national health security, in which the roles of the private sector and the government were mixed, should be gradually introduced. The major political groups, in particular, proposed to (1) set workers as beneficiaries of insurance, (2) share financial resources jointly among the state, employers, and workers, and (3) promote the expansion of the number of doctors and medical institutions and prefer cooperative operations of the hospitals established in small administrative units. This paper argues that the ideas on national health security during the liberation period did not completely deviate from the global trend immediately after World War II when countries tried to expand the number of people covered by national health security and strengthen its coverage. Although these ideas were not fully reflected in the Constitution of 1948, it is significant in that the Constitution codified for the first time the state’s responsibility for those who have no ability for living due to their health conditions.